The T-type calcium channel isoform Cav3.1 is a target for the hypnotic effect of the anaesthetic neurosteroid (3β, 5β, 17β)-3-hydroxyandrostane-17-carbonitrile. (January 2021) - Timic Stamenic, Tamara; Feseha, Simon; Manzella, Francesca M.; Wallace, Damon; Wilkey, Davis; Corrigan, Timothy; Fiedler, Hanna; Doerr, Patricia; Krishnan, Kathiresan; Raol, Yogendra H.; Covey, Douglas F.; Jevtovic-Todorovic, Vesna; et al.
Abstract: Background: The mechanisms underlying the role of T-type calcium channels (T-channels) in thalamocortical excitability and oscillations in vivo during neurosteroid-induced hypnosis are largely unknown. Methods: We used patch-clamp electrophysiological recordings from acute brain slices ex vivo, recordings of local field potentials (LFPs) from the central medial thalamic nucleus in vivo, and wild-type (WT) and Cav 3.1 knock-out mice to investigate the molecular mechanisms of hypnosis induced by the neurosteroid analogue (3β, 5β, 17β)-3-hydroxyandrostane-17-carbonitrile (3β-OH). Results: Patch-clamp recordings showed that 3β-OH inhibited isolated T-currents but had no effect on phasic or tonic γ-aminobutyric acid A currents. Also in acute brain slices, 3β-OH inhibited the spike firing mode more profoundly in WT than in Cav 3.1 knockout mice. Furthermore, 3β-OH significantly hyperpolarised neurones, reduced the amplitudes of low threshold spikes, and diminished rebound burst firing only in WT mice. We found that 80 mg kg −1 i.p. injections of 3β-OH induced hypnosis in >60% of WT mice but failed to induce hypnosis in the majority of mutant mice. A subhypnotic dose of 3β-OH (20 mg kg −1 i.p.) accelerated induction of hypnosis by isoflurane only in WT mice, but had similar effects on the maintenance of isoflurane-induced hypnosis in both WT and Cav 3.1 knockout mice. In vivo recordings of LFPs showed that a hypnotic dose of 3β-OH increased δ, θ, α, and β oscillations in WT mice in comparison with Cav 3.1 knock-out mice. Conclusions: The Cav 3.1 T-channel isoform is critical for diminished thalamocortical excitability and oscillations that underlie neurosteroid-induced hypnosis.